Assessment of the Ability of Shock Index to Predict Early Hemodynamic Collapse in Hypotensive Sepsis Patient in Emergency Department - Baloch , Aiesha; Ali, Waqas Farooq; Shoukat, Rafia; Asghar, Dania; Baloch , Aqsa; Sta Ines, Mars Christian Aragon (Indus Journal of Bioscience Research, 2025)
Background: Shock is defined as a state of decreased perfusion and oxygenation to distant tissues. There are multiple types of shock depending on its underlying cause. Objective: To determine the accuracy of the Shock Index in predicting the early hemodynamic collapse in hypotensive sepsis patients. Methodology: This Cross-sectional study was conducted at the Accident and Emergency Department, Mayo Hospital Lahore, from November 2023 to May 2024. In this study, 150 patients, of either gender with ages between 18-75 years, presenting to the accident and emergency department diagnosed with sepsis, were included. Employing non-probability consecutive sampling, patients were divided into Group A with shock index >0.87 and Group B with shock index <0.87. After initial resuscitation, patients were admitted to intensive care units and followed up for 05 days. Demographic characteristics, comorbidity, and hemodynamic collapse during the follow-up period were recorded. Results: In our study, 83 (55.3%) were males and 67 (44.6%) were females with a median (IQR) age of 45 (31.75-60.25) years. In patients from Group A, median duration of sepsis was 06 (3-8) days as compared to 5.50 (3-8) days in Group B. The majority of patients in Group A, i.e. 80 (53.3%) , were diabetic as compared to 70 patients (46.6%) with shock index <0.87. When the shock index was used as a predictor of hemodynamic collapse the sensitivity of the shock index was 77%, the specificity was 69.23%, and a diagnostic accuracy of 73.33% (p <0.001). Conclusion: The Shock Index is an accurate, easy-to-calculate, and interpretable tool for predicting early hemodynamic collapse in sepsis patients. In the future, it can serve as a valuable bedside tool for identifying sepsis patients at risk of hemodynamic deterioration.